Sex‐Based Differences in Thrombus Composition in Acute Ischemic Stroke - Ghil Schwarz; Angelo Cascio Rizzo; Amedeo Cervo; Martina Di Como; Maria Costanza Aquilano; Emanuele Valtorta; Guglielmo Carlo Pero; Mariangela Piano; Maria Sessa (Stroke: Vascular and Interventional Neurology)
Background Endovascular thrombectomy allows for detailed study of thrombus composition in acute ischemic stroke. Differences in thrombus composition can affect outcomes, and the impact of sex on coagulation physiology is recognized. This study investigates whether thrombus composition in acute ischemic stroke varies between sexes. Methods Retrospective study on consecutive endovascular thrombectomy‐treated patients with acute ischemic stroke at Niguarda Hospital in 2023. Thrombi were stained with hematoxylin and eosin, and the percentages of fibrin, red blood cells (RBCs), and white blood cells (WBCs) were quantified as proportions of the total thrombus area. Univariate and multivariate analyses were performed to identify histological differences between sexes—multivariate analysis adjusted for variables associated with each thrombus component with a P value <0.1. Results Seventy‐three cases (50.7% female) were included in the study. Male patients exhibited a higher percentage of RBCs within the thrombus (median 51.5% versus 33.8%, P = 0.004), whereas female patients had a higher percentage of fibrin (median 58.3% versus 45.1%, P = 0.020) and WBCs (median 6.5% versus 4.4%, P = 0.045). Univariate analysis indicated that sex was associated with all 3 thrombus components: fibrin (β = 10.08 [95% CI, 1.29–18.87], P = 0.025), RBCs (β = −12.12 [95% CI, l−21.04 to −3.21], P = 0.008), and WBCs (β = 2.05 [95% CI, 0.23–3.86], P = 0.028). In the multivariate analysis, sex lost its association with both fibrin and RBC percentages, and only baseline RBC count maintained its independent association with these 2 components. For the percentage of WBCs in the thrombus, both sex (β = 2.13 [95% CI, 0.25–4.01], P = 0.027) and stroke etiology (β = 0.81 [95% CI, 0.03–1.58], P = 0.041) showed significant and independent associations. Conclusion Our exploratory study shows that sex independently affects the percentage of WBCs in thrombi. The percentage of fibrin and RBC does not have an independent association with sex and may be mediated by different RBC count. Future research in this field should consider sex and baseline laboratory values.